2016
DOI: 10.1177/1077801216636241
|View full text |Cite
|
Sign up to set email alerts
|

Victimization and HIV Risks Among Croatian Female Sex Workers

Abstract: To assess the association between victimization and HIV vulnerability among Croatian female sex workers (FSWs), a survey involving 157 FSWs recruited from Croatia's two largest urban areas was conducted in 2014. A majority of participants reported direct and indirect victimization, which was found to be significantly associated with condom use at most recent noncommercial sexual intercourse and sexually transmitted infection (STI) diagnosis in the past 12 months. The association between victimization and STI d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 68 publications
(112 reference statements)
0
3
0
1
Order By: Relevance
“…That social support does not show to have a buffering role in HIV vulnerability among females is contradictory to findings from past studies. As these studies (e.g., [23, 67]) focused on female sex workers, rather than females drawn from a general population, the difference in results may be attributed to the variation of study samples. Literature has also suggested that varied sources of social and emotional support (e.g., informal vs. formal) and types of social networks (e.g., family, partners, friends) can result in different effect on HIV risk behaviors for females [38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…That social support does not show to have a buffering role in HIV vulnerability among females is contradictory to findings from past studies. As these studies (e.g., [23, 67]) focused on female sex workers, rather than females drawn from a general population, the difference in results may be attributed to the variation of study samples. Literature has also suggested that varied sources of social and emotional support (e.g., informal vs. formal) and types of social networks (e.g., family, partners, friends) can result in different effect on HIV risk behaviors for females [38].…”
Section: Discussionmentioning
confidence: 99%
“…There has been a rising interest in understanding the link between mental health problems and HIV risk behaviors. Specifically, mental health problems and HIV risk behaviors are correlated among men who have sex with men [1320], drug injection users [21, 22], female sex workers [23], immigrants [24, 25], transgender women [26], and in general population [2729]. Together, these studies indicate that people with mental health needs may have increased vulnerability to HIV risk behaviors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…En consecuencia, incrementa la victimización, puesto que justifica las agresiones (Comack & Seshia, 2010, en Štulhofer et al, 2016. Así, las trabajadoras sexuales podemos presentar un mayor índice de violencias padecidas, tanto por parte de nuestra pareja, como de los clientes o la policía (Štulhofer et al, 2016;Zhang et al, 2017).…”
Section: Descripción Del Estigma De Prostitutaunclassified